2017
DOI: 10.7717/peerj.3858
|View full text |Cite
|
Sign up to set email alerts
|

Learning performance and brain structure of artificially-reared honey bees fed with different quantities of food

Abstract: BackgroundArtificial rearing of honey bee larvae is an established method which enables to fully standardize the rearing environment and to manipulate the supplied diet to the brood. However, there are no studies which compare learning performance or neuroanatomic differences of artificially-reared (in-lab) bees in comparison with their in-hive reared counterparts.MethodsHere we tested how different quantities of food during larval development affect body size, brain morphology and learning ability of adult ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 69 publications
5
20
0
Order By: Relevance
“…Suitable carbendazim post-exposure risk evaluation samples were then prepared for RNA-Seq and qRT-PCR. Our previous in vitro larval-rearing revealed a 75 emergence rate, which was acceptable ( Brodschneider et al, 2009 ; Aupinel et al, 2010 ; Crailsheim et al, 2013 ; Wu et al, 2017 ), and demonstrated the reliability of the present results.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Suitable carbendazim post-exposure risk evaluation samples were then prepared for RNA-Seq and qRT-PCR. Our previous in vitro larval-rearing revealed a 75 emergence rate, which was acceptable ( Brodschneider et al, 2009 ; Aupinel et al, 2010 ; Crailsheim et al, 2013 ; Wu et al, 2017 ), and demonstrated the reliability of the present results.…”
Section: Discussionsupporting
confidence: 85%
“…Rearing honeybee larvae in vitro is of great importance for research on pathogens and risk assessment ( Crailsheim et al, 2013 ). In the present study, honeybees were exposed to the fungicide carbendazim to assess and evaluate its sublethal effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another explanation for workers' smaller MB calyces, and whole brains as well, is that larval nutrition may influence neural development. Larval nutrition affects brain morphology in honeybees, with queens having larger and more rapidly growing brains in the larval stage (Moda et al , ), and reduced larval nutrition results in smaller MB calyces at emergence in workers (Steijven et al , ), but this has not been studied in primitively eusocial groups. Variation in larval nutrition can affect reproductive physiology and behavior in other sweat bee species (Richards and Packer, ; Brand and Chapuisat, ) as well as other species of primitively eusocial insects (Judd et al , ; Lawson et al , ; ; Kapheim, ).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the in vitro rearing procedure (details in Sections 2.2 and 2.3) has been developed as a way to assess potential stressors during the development of bees under laboratory conditions (Becker and Keller 2016;Crailsheim et al 2013). Nevertheless, only a few studies have compared artificially reared brood with honey bees reared in the hive (Brodschneider et al 2009;De Souza et al 2015;Steijven et al 2017).…”
Section: Introductionmentioning
confidence: 99%